PENGARUH PEMBIASAAN MEMBACA AL-QUR’AN PADA AWAL PEMBELAJARAN DI MAN 19 JAKARTA - Heru Wibowo (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
The purpose of this research is to determine whether there is a disclosure of the effect of the habit of reading the Qur'an at the beginning of learning on the learning outcomes of Islamic Religious Education students of class XII MAN 19 Jakarta. This study involved students from class XII-A to class XII — F with 66 students. The research method used is quantitative with an analytical approach using statistical methods, namely the IBM SPSS Statistic 25 application. The results of this study indicate that there is a positive influence on the habit of reading the Qur'an on the learning outcomes of Islamic Religious Education. A simple linear regression analysis shows the value of 2.040 and 1.999. The significance value is 0.046 < 0.05. Thus Ha is accepted and Ho is rejected, which means that there is a significant influence on the habit of reading the Qur'an at the beginning of learning on the learning outcomes of Islamic Religious Education class XII MAN 19 Jakarta.